PENGARUH BAURAN PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN PT. BATIK DANAR HADI MEDAN - Nova Banjarnahor; Henri Saragih; Mangasa Panjaitan (Universitas Methodist Indonesia, 2020)
The purpose of this study was to determine and analyze the effect of advertising, sales promotion, public relations and direct marketing simultaneously on increasing sales volume. The number of research samples was 97 people. The data analysis method used multiple linear regression. The results showed that advertising had a positive and significant effect on sales volume. Sales promotion has a positive and significant effect on sales volume. Public relations has a positive and significant effect on sales volume. Direct marketing has no effect on sales volume. Advertising, sales promotion, public relations, and direct marketing have a positive and significant effect on sales volume.